2023
DOI: 10.3390/agronomy13020308
|View full text |Cite
|
Sign up to set email alerts
|

Water and Nitrogen Regulation Effects and System Optimization for Potato (Solanum tuberosum L.) under Film Drip Irrigation in the Dry Zone of Ningxia China

Abstract: Potatoes require water and fertilizer management systems to optimize economic outcomes and fertilizer use, especially in arid areas such as Ningxia, China. In this study, three irrigation quotas (1200 (W1), 1650 (W2), and 2100 (W3) m3/hm2) and three nitrogen application treatments (110 (N1), 190 (N2), and 270 (N3) kg/hm2) were evaluated. Potato growth, final yield, and quality indices were assessed in relation to fertility periods, irrigation utilization efficiency, nitrogen and fertilizer bias productivity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…These findings are similar to those of Song et al [44], who conducted a study in Qinghai, China, and Ma et al [45], who conducted a study in Ningxia, China, on wolfberry, both indicating that appropriate water deficit and reduced nitrogen application are conducive to stress resistance, and too little or too much water and nitrogen inputs are not conducive to crop growth [46]. Similar to the findings of Zhang et al [47], who conducted research on spinach in Shanghai, China, and Yang et al [48], who conducted studies on potatoes in Ningxia, China, this study also concluded that the interaction of water regulation and nitrogen application levels significantly affected plant height and stem diameter growth amount in wolfberry. This was mainly because an adequate water and nitrogen ratio can provide a suitable moisture and nutrient-rich environment for crop growth and development [49,50].…”
Section: Effects Of Water and Nitrogen Regulation On The Growth And P...supporting
confidence: 55%
“…These findings are similar to those of Song et al [44], who conducted a study in Qinghai, China, and Ma et al [45], who conducted a study in Ningxia, China, on wolfberry, both indicating that appropriate water deficit and reduced nitrogen application are conducive to stress resistance, and too little or too much water and nitrogen inputs are not conducive to crop growth [46]. Similar to the findings of Zhang et al [47], who conducted research on spinach in Shanghai, China, and Yang et al [48], who conducted studies on potatoes in Ningxia, China, this study also concluded that the interaction of water regulation and nitrogen application levels significantly affected plant height and stem diameter growth amount in wolfberry. This was mainly because an adequate water and nitrogen ratio can provide a suitable moisture and nutrient-rich environment for crop growth and development [49,50].…”
Section: Effects Of Water and Nitrogen Regulation On The Growth And P...supporting
confidence: 55%
“…Like TP, total nitrogen (TN) is also an important water quality parameter for investigating eutrophication of lakes and reservoirs [21]. TN represents the combination of various organic and inorganic nitrogen species into a single measure [22]. As seen in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…When crops suffered from drought stress during the growth period, the antioxidant enzyme system was activated to protect cells from oxidative damage, causing blockage of primary metabolite synthesis pathways and insufficient raw materials for secondary metabolite synthesis, which led to yield reduction [41]. However, reasonable soil moisture increased potato root vigor and enlarged the root-soil contact area, which improved the metabolic rate of the crop [42]. In addition, appropriate irrigation significantly reduced plant canopy temperature, increased environmental humidity, reduced soil moisture loss from evaporation, and alleviated drought stress during the whole growth period, which ultimately promoted crop yield formation [43].…”
Section: Plant Height Ty and Nimentioning
confidence: 99%